Local Wisdom Of The People Of Kemlaten Village Parengan Sub-District In Utilizing Wild Plants - Aprilia, Diah Ayu; Cintamulya, Imas (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
The community of Kemlaten village has a habit of using wild plants as food and medicine. The purpose of this study was to describe the types of wild plants used by the Kemlaten village community, Parengan District, as food and medicine and as well as their morphology. This quantitative descriptive study was conducted in March-April 2022 in the Kemlaten village area. The results of the study showed that there were 25 species of wild plants used as food and medicine by the Kemlaten villagers. Of the 25 wild plant species, 32% are used as food and 68% as medicine. The results of the morphological analysis of wild plants used as food and medicine by the villagers of Kemlaten are dominated by single-leaf plants and woody stems. The morphology of these wild plants differs from one another according to the type or family of these wild plants.